2022
DOI: 10.1101/2022.02.08.479540
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-excitation Raman Spectroscopy Complements Whole Genome Sequencing for Rapid Detection of Bacterial Infection and Resistance in WHO Priority Pathogens

Abstract: Current methods for diagnosing acute and complex infections mostly rely on culture-based methods and, for biofilms, fluorescence in-situ hybridization. These techniques are labor-intensive and can take 2-4 days to return a test result, especially considering an extra culturing step required for the antibiotic susceptibility testing (AST). This places a significant burden on healthcare providers, delaying treatment and leading to adverse patient outcomes. Here, we report the complementary use of our newly deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The wild-type/sensitive and phenotypically resistant/non-wild-type strains of Gram-negative Acinetobacter baumannii (n=6), Escherichia coli (n=7), Klebsiella pneumoniae (n=5), and Grampositive Staphylococcus aureus (n=2), Bacillus subtilis (n=1) were used for this study. Phenotypic information on E. coli, K. pneumoniae, and S. aureus strains was previously reported in [6,16,36]. Minimum inhibitory concentration (MIC) values of Acinetobacter strains were as described in [37].…”
Section: Bacterial Strains and Phenotypic Assessmentmentioning
confidence: 99%
See 3 more Smart Citations
“…The wild-type/sensitive and phenotypically resistant/non-wild-type strains of Gram-negative Acinetobacter baumannii (n=6), Escherichia coli (n=7), Klebsiella pneumoniae (n=5), and Grampositive Staphylococcus aureus (n=2), Bacillus subtilis (n=1) were used for this study. Phenotypic information on E. coli, K. pneumoniae, and S. aureus strains was previously reported in [6,16,36]. Minimum inhibitory concentration (MIC) values of Acinetobacter strains were as described in [37].…”
Section: Bacterial Strains and Phenotypic Assessmentmentioning
confidence: 99%
“…Culture-independent diagnostic tests can also detect dead bacteria when antibiotic therapy has been administered before sampling [12]. Label-free optical techniques such as quantitative phase microscopy [13] and Raman spectroscopy [14, 15] have recently been shown to measure phenotypic and molecular signatures in pathogens at very low concentrations. We have recently reported the multi-excitation Raman spectroscopy (ME-RS) method for the species, resistance, and strain-level classification of pathogens [16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Real-time sequencing, for example, has been successfully implemented in lower respiratory tract infections, urine infections, cerebral spinal fluid, surgical site infections, and orthopedic devices with up to 100% sensitivity and specificity in the pathogen detection ( Wang et al, 2020 ; Whittle et al, 2022 ). Label-free optical techniques such as quantitative phase microscopy ( Kim et al, 2022 ) and Raman spectroscopy ( Ho et al, 2019 ; Lister et al, 2022 ) have recently been shown to measure phenotypic and molecular signatures in pathogens at very low concentrations. Oh et al (2020) utilized optical diffraction tomography to quantitatively analyze the response of Escherichia coli and Bacillus subtilis to varying concentrations of ampicillin ( Oh et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%